Old stories and new chapters: a biographical study of white Afrikaans speaking identity in central South Africa - Kotze, Paul Conrad (University of the Free State, 2013)
Since the fall of apartheid and the emergence of a wholly democratic South Africa in 1994, little research has been done on the topic of white identity in this rapidly transforming multicultural society. Indeed, apart from an array of popular books on the subject, there has been virtually no academic interest in the question of how white South Africans have reconstructed their individual and collective identities since the fall of apartheid, and the resulting erosion of the ready answers previously provided to them regarding questions of belonging and identification. This study set out to remedy this situation through exploring the identities that white South Africans, and white Afrikaans speakers in particular, have constructed out of the wreckage of the 20th century. Embracing a qualitative approach, this study focused on exploring stories of contemporary white Afrikaans speaking identity as told in the participants’ own words. Six individuals, ranging from students in their late teens to a grandson of Hendrik Verwoerd, shared their stories, which were reflexively engaged through an interpretive sociological approach that incorporated elements of phenomenology, existentialism and reflexive sociology. The dissertation starts off with an introduction to the epistemological and ontological foundation upon which the investigative process was built, before investigating the concept identity as conceptualised during the research process, namely as constituting a relatively stable but malleable set of understandings regarding the self and its place within society in general and specific racial, religious and cultural collectivities in particular. A history of white Afrikaans speaking identity is then presented, which makes clear the prior existence of at least three historical white Afrikaans speaking collectivities, namely the Burghers of the 17th and 18th centuries, the Boers of the 1800’s, and the Afrikaners of the 20th century. The stage is then set for the examination of the new collectivities that have developed since the demise of a coherent Afrikaner identity in the late 20th century. The data, collected by means of reflexive individual and group interviews, and analysed using ‘Dialogical Narrative Analysis’ (DNA), a process that focuses on the contents and circulation of individual and collectively shared stories, or ‘narrative repertoires’, indicate the existence of at least three relatively coherent contemporary white Afrikaans speaking collectivities. These are the ‘Pseudo-Boers’, the ‘Afrikaners’, and the ‘Afrikaanses’. These three collectivities, developing simultaneously and largely parallel to each other out of the once coherent Afrikaner collectivity of the previous century, exhibit significant variance regarding the content, structure and circulation of their narrative repertoires. This means that Afrikaners, Pseudo-Boers and Afrikaanses, on both the individual and collective levels, differ from each other in terms of the stories they tell and dynamics pertaining to the circulation of these stories, as well as the genres, plots and character types prevalent in them. These shared stories in turn represent, according to this study, the matrix out of which identity is constructed, be it individual or collective. The uncovered data are further represented in a manner borrowing from certain techniques used in the fields of semi-fiction writing and journalism, with the aim to aid understanding through presenting the data themselves in a storied form. This choice was made in line with the hypothesis, developed throughout this dissertation, that the uniquely human phenomenon of storytelling in fact underlies much of the social construction of reality, and serves to inform individual and collectively shared meaning frameworks and understandings regarding the world of everyday life.
Dissertation (M.A. (Sociology))--University of the Free State, 2013
Keywords: Afrikaners -- South Africa -- Ethnic identity; Discourse analysis, Narrative; Afrikaners -- South Africa -- History; Phenomenology; Identity; Mystery; Pseudo-Boer; Dialogical narrative; Narrative repertoire; White Afrikaans speaker; Dialogical narrative analysis